2019
DOI: 10.4103/ijciis.ijciis_67_18
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic sternal injury in patients with rib fracture: A single-center experience

Abstract: Purpose: We aimed to assess the pattern and impact of sternal injury with rib fracture in a Level 1 trauma center. Patients and Methods: We conducted a retrospective review of trauma registry data to identify patients who presented with sternal fracture between 2010 and 2017. Data were analyzed and compared in patients with and without rib fracture. Results: We identified 212 patients with traumatic sternal injury, of them 119 (56%) had assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…In previous studies, rib fractures were identified in up to 56% of cases of multiple trauma [8,[13][14][15], which is in accordance with our results. The delayed diagnosis of a rib fracture may lead to persistent pain, loss of functional lung capacity, pulmonary complications, and prolonged hospitalization [8,14].…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, rib fractures were identified in up to 56% of cases of multiple trauma [8,[13][14][15], which is in accordance with our results. The delayed diagnosis of a rib fracture may lead to persistent pain, loss of functional lung capacity, pulmonary complications, and prolonged hospitalization [8,14].…”
Section: Discussionsupporting
confidence: 93%
“…The mortality of SFs admitted was low at 8%, 30 days post injury. Again, this remains in line with other evidence to suggest that although injury severity can be high, mortality remains low [ 14 , 16 , 17 ]. Assessments performed by Simsek et al highlighted a mortality rate of 11.1% in 115 patients with SF where mortality rates were significantly higher in comminuted SFs ( p = 0.045).…”
Section: Discussionsupporting
confidence: 89%
“…Concomitant injuries alongside rib fractures such as haemothorax and lung contusions were more evident in their analysis of SF patients. [ 14 ] This evidence is also supported by Yakar et al [ 15 ] who identified that MVA was the most common mechanism of injury in their SF patients (66.4%, N = 128) and the most common thoracic pathology accompanying SFs was rib fractures (36%, N = 128). Despite the evidence displaying the prevalence of rib fractures and its associated risk in the context of SF, there is very little evidence to review regarding bilateral rib injury.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Before induction of general anesthesia, high oxygen concentration will make the lung foam disappear; the use of anesthetics and muscle relaxation can cause the patient to relax the muscles in the lungs, resulting in a decrease in the tension of the elastic contractive diaphragm on the lateral side of the chest wall; during the process of anesthesia, increased secretions such as alveoli small airway blockage lead to atelectasis. Under anesthesia, the ventilation and blood perfusion status of patients changes, and the ventilation volume in the middle and lower regions decreases, resulting in the condition of hypoventilation [18,19].…”
Section: Discussionmentioning
confidence: 99%